2021
DOI: 10.1111/jvim.16211
|View full text |Cite
|
Sign up to set email alerts
|

Puppyhood diet as a factor in the development of owner‐reported allergy/atopy skin signs in adult dogs in Finland

Abstract: Background The increased prevalence of atopic dermatitis (AD) in dogs necessitates research in its disease etiology. Objectives To explore the association between puppyhood dietary exposures and prevalence of owner‐reported allergy/atopy skin signs (AASS) after the age of 1 year. Animals Four thousand and twenty‐two dogs were eligible, 1158 cases, and 2864 controls. Methods This cross‐sectional hypothesis‐driven observational study was extracted from the DogRisk food frequency questionnaire. Forty‐six food ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 91 publications
(115 reference statements)
3
5
0
Order By: Relevance
“…Feeding with fish oil during puppyhood also showed a significant protective association in the unadjusted analysis. In a previous study looking for dietary risk factors of allergy/atopy skin signs during puppyhood we found that fish oil was significantly associated with a lower incidence of allergy/atopy skin signs when given once per year while giving the fish oil supplement frequently or several times per week was associated significantly with a high risk of allergy/atopy skin signs in dogs ( 57 ). We will now put our results into a wider perspective of nutritional fats and epilepsy.…”
Section: Discussionmentioning
confidence: 94%
“…Feeding with fish oil during puppyhood also showed a significant protective association in the unadjusted analysis. In a previous study looking for dietary risk factors of allergy/atopy skin signs during puppyhood we found that fish oil was significantly associated with a lower incidence of allergy/atopy skin signs when given once per year while giving the fish oil supplement frequently or several times per week was associated significantly with a high risk of allergy/atopy skin signs in dogs ( 57 ). We will now put our results into a wider perspective of nutritional fats and epilepsy.…”
Section: Discussionmentioning
confidence: 94%
“…The FFQ included different categories of questions regarding the dogs' disease diagnoses and life-long exposures, including nutrition of the dog and its dam, environmental indoor and outdoor exposures, history of maternal diseases, breed, sex, age, coat color, etc. More information on the FFQ has been presented in prior research (19)(20)(21)(22)24). The FFQ was approved by the ethical board of Viikki campus, University of Helsinki (29.4.2016).…”
Section: Data Source and Outcome Measurementioning
confidence: 99%
“…From the latter we only analyzed two extreme groups; the dogs that had either been eating over 80% of UPCD or over 20% of NPMD in their diets. These percentages were chosen based on previous research (21). Additionally, we examined two ratio scales to evaluate the prevalence of otitis among the study sample when consuming different ratios (0%, 1-25%, 26-50%, 51-75%, 76-100%) of the two, NPMD and UPCD, feeding patterns.…”
Section: Study Setting Design and Early-life Tested Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…These type of diets are perceived as more nutritious and natural as the components are not heated and mantain the thermosensitive components, which are associated with a series of potential benefits including improved behaviour, shinier coat, better palatability and prevention of disorders affecting body systems (Davies et al, 2019;Freeman et al, 2013). In this respect, for instance, a recent observational study found significantly lower allergy/atopy skin signs after the age of 1 year in dogs eating more than 20% of diet as raw (Hemida et al, 2021).…”
Section: Introductionmentioning
confidence: 99%